2007
DOI: 10.1080/09540120601095734
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of alcohol consumption on survival for HIV+ individuals

Abstract: Alcohol consumption is associated with decreased antiretroviral adherence, and decreased adherence results in poorer outcomes. However the magnitude of alcohol's impact on survival is unknown. Our objective was to use a calibrated and validated simulation of HIV disease to estimate the impact of alcohol on survival. We incorporated clinical data describing the temporal and dose-response relationships between alcohol consumption and adherence in a large observational cohort (N = 2,702). Individuals were categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 39 publications
1
109
1
2
Order By: Relevance
“…Rego 23 avaliaram uma coorte com mais de 2.500 pessoas convivendo com o vírus HIV e estimou que o uso pesado de álcool (≥ 5 doses/ dia de consumo) pode reduzir a sobrevida desses indivíduos, em média, em mais de três anos se o consumo é semanal e em mais de seis anos quando o consumo é diário. Também foi estimada uma redução na sobrevida dos indivíduos com uso moderado (< 5 doses/dia de consumo), sendo, em mé-dia, maior que um ano em pessoas com consumo semanal e maior que três anos quando o consumo é diário 23 .…”
Section: Resultsunclassified
“…Rego 23 avaliaram uma coorte com mais de 2.500 pessoas convivendo com o vírus HIV e estimou que o uso pesado de álcool (≥ 5 doses/ dia de consumo) pode reduzir a sobrevida desses indivíduos, em média, em mais de três anos se o consumo é semanal e em mais de seis anos quando o consumo é diário. Também foi estimada uma redução na sobrevida dos indivíduos com uso moderado (< 5 doses/dia de consumo), sendo, em mé-dia, maior que um ano em pessoas com consumo semanal e maior que três anos quando o consumo é diário 23 .…”
Section: Resultsunclassified
“…Furthermore, studies have shown that individuals with alcohol use disorders have an increased risk of contracting HIV and similarly, alcohol-related problems are common among HIV+ individuals, both of which could have significant implications for the further expansion of the HIV epidemic (Braithwaite et al, 2007;Samet et al, 2007;Shaffer, Njeri, Justice, Odero & Tierney, 2004).…”
Section: Alcohol Use and Hiv Sexual Risk Behavioursmentioning
confidence: 99%
“…Hazardous alcohol use (≥5 standard drinks on drinking days) decreased overall survival by more than 3 years if frequency of consumption was once per week or more, and by 6.4 years with daily use (Braithwaite et al, 2007). In addition, the effect of alcohol on liver function may affect its ability to metabolise certain HIV medication, thus reducing their therapeutic efficacy.…”
Section: Alcohol Use and Hiv Infection Disease Progression And Treatmentioning
confidence: 99%
“…Alcohol use can lead to decreased antiretroviral medication adherence and worse biologic outcomes such as decreased cluster of differentiation 4 (CD4) cell count and increased HIV viral load, even in the current era of combined antiretroviral therapy (cART) (Braithwaite et al, 2007(Braithwaite et al, , 2008Romeo et al, 2007;Samet et al, 2004bSamet et al, , 2007. Finally, alcohol use leads to a loss of inhibition and therefore is associated with behaviors that increase the risk of acquiring or transmitting HIV, such as unprotected sex and multiple sexual partners (Fiellin, 2004;Justice et al, 2010).…”
mentioning
confidence: 99%